Bioclimatic drivers of forage growth and cover in alpine rangelands - Wang, Li; Ma, Wenmei; Zhou, Dan; Chen, Qi; Liu, Lu; Li, Long (Frontiers in Ecology and Evolution, 2023)
Abstract Context: Climate change and anthropogenic activities have had considerable impacts on the Qinghai–Tibetan Plateau. As a result, the alpine ecosystem in this region has undergone some degree of degradation. A decline in forage yield reduces the livestock carrying capacity, whereas an unmitigated increase may lead to overfeeding and damage to the vegetation. These changes eventually lead to grassland degradation and a series of ecological problems. Therefore, it is essential to examine the bioclimatic factors affecting forage growth in grasslands. Objective: To identify the bioclimatic factors associated with forage growth and coverage in the Qinghai–Tibetan Plateau. Methods: We examined how forage growth and coverage were affected by 35 bioclimatic indicators published in a global database (CMCC-BioClimInd). Results and Conclusions: Forage yield was significantly correlated with 16 bioclimatic indexes. It showed positive correlations with Bio24 (annual positive precipitation; R2=0.49), Bio12 (annual precipitation; R2=0.48), and Bio17 (precipitation in the driest quarter; R2=0.47); and negative correlations with Bio4 (temperature seasonality; R2=0.52), Bio15 (precipitation seasonality; R2=0.39), and Bio27 (simplified continentality index; R2=0.48). Forage coverage was significantly correlated with 15 bioclimate indicators. It showed positive correlations with Bio17 (precipitation in the driest quarter; R2=0.36), Bio14 (precipitation in the driest month; R2=0.33), and Bio12 (annual precipitation; R2=0.31); and negative correlations with Bio4 (temperature seasonality; R2=0.415), Bio7 (annual temperature range), Bio15 (precipitation seasonality), and Bio27 (simplified continentality index; R2=0.37). Significance: We identified the bioclimatic indicators that affect forage growth in the northeast region of the Qinghai–Tibetan Plateau. Based on this, we explore the physiological and ecological mechanisms underlying forage growth. Or results provide a scientific basis for future forage management, early determination of livestock carrying capacity, rational management of animal husbandry practices, and ecological protection and restoration efforts.